2020
DOI: 10.3390/jcm9030713
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cervical Spine Alignment and its Relationship with Other Spinopelvic Parameters after Laminoplasty in Patients with Degenerative Cervical Myelopathy

Abstract: For patients with kyphosis of the cervical spine, laminoplasty is usually incapable of improving neurological symptoms as it worsens kyphotic alignment. Thus, laminoplasty is not recommended in the presence of kyphotic alignment. Nevertheless, laminoplasty may be selected for myelopathy due to multiple-segment intervertebral disc herniation or ossification of posterior longitudinal ligament despite kyphotic alignment. This study examined whether cervical alignment influences surgical outcomes. Cervical alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Previous studies showed that cervical sagittal alignment plays an important role in the clinical outcomes of laminoplasty. If the patient's lordotic alignment of the cervical spine is well maintained, the outcome of the surgery is always good [ 4 ]. On the other hand, the straight or kyphotic curvature of the cervical spine is not recommended as a good indication for laminoplasty because the laminoplasty may not create enough posterior migration of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that cervical sagittal alignment plays an important role in the clinical outcomes of laminoplasty. If the patient's lordotic alignment of the cervical spine is well maintained, the outcome of the surgery is always good [ 4 ]. On the other hand, the straight or kyphotic curvature of the cervical spine is not recommended as a good indication for laminoplasty because the laminoplasty may not create enough posterior migration of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the Cobb angle method was typically used for assessment of CSA. However, this method does not allow for precise assessment of the segmental deformities [ 3 6 ]. Owing to the segmental deformities, results of Cobb angle method for assessment of cervical alignment may be misleading, especially in patients with cervical kyphosis (CK).…”
Section: Introductionmentioning
confidence: 99%
“…However, this method does not allow for precise assessment of the segmental deformities [3][4][5][6] . Owing to the segmental deformities, results of Cobb angle method for assessment of cervical alignment may be misleading, especially in patients with cervical kyphosis (CK).…”
Section: Introductionmentioning
confidence: 99%